The Use of Student-Centered Learning Method For Speaking Skill in EFL Classroom - Gunawan Indrapurnama; Fakhruddin, Afief; Kustini, Titin (Papanda Publisher, 2022)
The objective of this research is to find out the effectiveness of using the Student-Centered Learning (SCL) method to develop the speaking skill of second grade students. This research applied classrooom action research. The population of this research was the second-grade students that were XI IPA as experimental class and the research sample was selected using purposive sampling technique to determine the sample. The data were collected through pre-test and post-test. Data were analyzed using formula to calculating the mean score of the pre-test and the post-test. The results showed that the mean differences between using Teacher-Centered Learning method and when using Student-Centered Learning method. Pre-test result got 14.3 score and Post-test 17.56, which means that the use of SCL has an impact on students speaking achievement.